0369 Sleep Education for the Nurse Practitioner: Nurse Practitioner Student Focus Group Findings. (25th May 2022) - Watach, Alexa; McPhillips, Miranda; Saconi, Bruno; Lang-Gallagher, Rebecca; Lyons, M Melanie; Renz, Susan; Rosen, Ilene; Sawyer, Amy
Abstract: Introduction: Primary care nurse practitioners (NPs) receive little to no sleep education in graduate programs despite being first-line providers for patients presenting with sleep-related symptoms. Sleep curriculum has been consistently identified as a gap in nursing education and confirmed in recent survey studies of nurses and NPs. Methods: Qualitative descriptive study to explore NP students' reactions to an asynchronous, case-based sleep e-learning program. Data were collected as part of a larger pre-/post-study assessing the program. Six asynchronous online modules were offered to a cohort of primary care NP students in a single academic institution's master's degree in primary care nursing program. At the end of the course, students were invited to participate in one-hour, online, focus group sessions. Directed content analysis, guided by the Kirkpatrick training evaluation model, was used to analyze the qualitative data to understand NP students' experience with the program and elicit their perspectives about sleep education. Results: Participants in the course (N=67) were predominantly female (88%) and ≤35 years old (81%). Twenty-four students participated in the focus group sessions. Two overarching themes emerged, including positive reactions to (1) course design and (2) course content. Students reported the case-based scenarios and quizzes enhanced their learning and kept them engaged, noted the user-friendly format, and appreciated that the course was asynchronous. After completing the modules, students recognized they had a previous knowledge gap related to sleep and perceived the information they received to be relevant to their practice/patient population and to their own personal health/wellbeing. Students also discussed their intentions to incorporate sleep assessments into practice. Conclusion: Given the increasing sleep health needs of the population and the growing shortages of sleep providers, there is a critical need to ensure NP's have the proper education to recognize and identify implications of poor and disordered sleep in their patients. In this study, NP students enthusiastically embraced sleep education, identified knowledge gain, and had intentions to apply their learned skills in practice highlighting the feasibility of increasing curricular exposure to sleep medicine. Support (If Any): The work reported herein was supported by National Institutes of Health (R25HL120874 Rosen, PI).